2012
DOI: 10.1021/jp303297c
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nuclear Magnetic Relaxation To Elucidate Proton Location and Dynamics in N···H···O Hydrogen Bonds

Abstract: The proton location and dynamics in a hydrogen bond in solution are fundamentally important for understanding the phenomenon of proton transfer (PT). In the present study, the proton location and its dynamics were explored for the NH form of the two PT tautomers of the Schiff base by analyzing the fluctuation of the (15)N-(1)H magnetic dipolar coupling by the PT as well as the NH reorientational motion. For this purpose, the (15)N and (13)C spin-lattice relaxation times were measured in dichloromethane or acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…When the system involves a PT process, the proton jump is accompanied by a change in the distance between the nitrogen and hydrogen atoms, and it produces a field fluctuation that contributes to the longitudinal relaxation of the 15 N magnetization, just like the NH reorientation. [31][32][33]78 However, the T 1 dd (NH) value only depends on the NH distances and the reorientational correlation time about the NH vector, τ R(NH) , when the PT is much faster or slower than the reorientational motion. In the slow PT limit, that is, when τ PT ≫ τ R(NH) (τ PT denotes the average lifetime of the proton on the nitrogen atom), T 1 dd (NH) −1 is represented as the average of the T 1 dd−1 values for the respective proton-bonded and nonbonded nitrogen atoms, as shown in eq 1 if one assumes a linear hydrogen bond under an extreme narrowing limit, τ R(NH)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the system involves a PT process, the proton jump is accompanied by a change in the distance between the nitrogen and hydrogen atoms, and it produces a field fluctuation that contributes to the longitudinal relaxation of the 15 N magnetization, just like the NH reorientation. [31][32][33]78 However, the T 1 dd (NH) value only depends on the NH distances and the reorientational correlation time about the NH vector, τ R(NH) , when the PT is much faster or slower than the reorientational motion. In the slow PT limit, that is, when τ PT ≫ τ R(NH) (τ PT denotes the average lifetime of the proton on the nitrogen atom), T 1 dd (NH) −1 is represented as the average of the T 1 dd−1 values for the respective proton-bonded and nonbonded nitrogen atoms, as shown in eq 1 if one assumes a linear hydrogen bond under an extreme narrowing limit, τ R(NH)…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Recently one of the authors demonstrated that O−H or N−H distances and ultrafast (∼10 11 s −1 ) PT rates can be obtained for intramolecular (or intradimer) short O−H−O and N−H−O hydrogen-bonded systems in solution by 17 O or 15 N spin− lattice relaxation measurements based on the fact that the 17 O− 1 H or 15 N− 1 H magnetic dipolar interaction fluctuates due to PT and O−H or N−H reorientational motion. 32,33 Computational approaches such as first-principles molecular dynamics simulation can be a complementary methodology for understanding the PT potential surfaces and dynamical behaviors of hydrogen-bonded systems. The Car−Parrinello molecular dynamics (CPMD) 34,35 has widely been applied to low-barrier hydrogen bonds in solution 36 and crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrafast dynamics of electronic ground state reactivity are not always accessible. In fact, many systems rely on a photoexcited reactive state (e.g., photoacid H + transfer, semiconductor/dye e – transfer, and photoinitiators). An interesting reactive intermediate is that of charged radicals generated by the ultrafast dissociation of ion pairs created via the direct excitation of the charge transfer (CT) band of nonbonded bimolecular complexes (Figure S1). Of particular relevance are small-molecule radical ions, which have shown interesting reactivity in protic media. Importantly, these photogenerated radicals are neither the result of electronic transitions that occupy a high-lying orbital by depopulating a low-energy orbital in the same molecule nor the outcome of molecular cleavage (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen-bonding is a highly directional and specific noncovalent interaction present in many organic and inorganic (bio)­molecules and materials and is responsible for the supramolecular assembly of biomacromolecules (protein folding, DNA base pairing, etc. ). Moreover, the proton location and its dynamics in a hydrogen bond in solution are of paramount importance for understanding the proton transfer reactions occurring in several chemical and biological systems. Hydrogen-bonding interactions have been extensively exploited in the field of organic crystal engineering and play a fundamental role for the ordering and self-organization of functional materials . Therefore, the study of the location and motion of protons is of particular interest for numerous applications in materials science, including catalysis (location of acid sites), organic semiconductor devices, fuel cells, optoelectronic devices (liquid crystals), and detection (sensors).…”
Section: Introductionmentioning
confidence: 99%